TEMA: Uso de dos sistemas de alimentación en cuyes (Cavia porcellus) en la etapa de cría, crecimiento, engorde en la zona tropical del Ecuador - Vergara Párraga, Gabriel Eduardo (2023)
In recent years, guinea pig meat has gained popularity in all regions of Ecuador due to its high nutritional value compared to other meats. For this reason, the production of this small species has experienced a significant boom. In this work, the benefits of using two feeding systems in the breeding, development and fattening stages of guinea pigs were evaluated. The feeding systems were based on the implementation of pigeon pea shell meal and the use of concentrate. Variables such as weight gain, food consumption, carcass yield, average weight, food conversion and cost benefit were evaluated through weekly weighings. An experimental unit composed of 32 female guinea pigs was used, which were divided into two blocks and 16 animals were placed per block. Four animals per treatment were used, with three treatments plus the control and two repetitions, to compare the benefit provided by the consumption of pigeon pea husk meal and the concentrate with different levels of consumption.The pigeon pea shell is a by-product considered as waste, used as a feeding alternative in the production of beef cattle. The chemical composition of this shell contains macro and micronutrients such as a good percentage of proteins, carbohydrates, vitamins, minerals and other components that help to gain weight and sustain the animals that consume it. The results obtained in this study show that the pigeon pea husk meal together with the concentrate gave higher weight gains with an average of 492 grams of weight gain greater than the other treatments. In addition, the use of the pigeon pea shell could be a sustainable and economic strategy for the production of guinea pig meat in Ecuador.